2014
DOI: 10.1007/s10396-014-0594-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypopharyngeal perforation caused by intraoperative transesophageal echocardiography

Abstract: Intraoperative transesophageal echocardiography (TEE) is an invaluable tool for cardiac surgical decision-making. TEE is considered reasonably noninvasive and safe, but insertion and manipulation of the TEE probe can lead to complications. Here, we report a patient with aortic stenosis who experienced TEE-associated hypopharyngeal perforation at the pyriform sinus complicated by esophageal trauma, pneumomediastinum and pneumoretroperitoneum. Based on this case, we suggest that rare complications be kept in min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In his review of 35 cases of EP, Sainathan reported that 75% occurred when TEE was performed in the operating room during cardiac surgery. Other case reports of TEE induced EP also occurred in an intraoperative setting [[7], [8], [9], [10], [11]]. The reason for this higher risk during intraoperative TEE may be explained by the prolonged, continuous pressure of the TEE probe to the esophageal mucosa, added to the possible low blood circulation in the esophagus during a cardiac surgery.…”
Section: Discussionmentioning
confidence: 98%
“…In his review of 35 cases of EP, Sainathan reported that 75% occurred when TEE was performed in the operating room during cardiac surgery. Other case reports of TEE induced EP also occurred in an intraoperative setting [[7], [8], [9], [10], [11]]. The reason for this higher risk during intraoperative TEE may be explained by the prolonged, continuous pressure of the TEE probe to the esophageal mucosa, added to the possible low blood circulation in the esophagus during a cardiac surgery.…”
Section: Discussionmentioning
confidence: 98%
“…These include Mallory-Weiss tear, oesophageal stenosis, Barrett’s oesophagus, Zenker’s diverticulum, tumour or strictures. Medications which may affect the integrity of oesophageal mucosae such as corticosteroids and bisphosphonates also increases the risk of oesophageal injury [2,7,8]. It is essential to note, however, that most cases of oesophageal perforation occur in patients with perceived low risk and hence, screening for predisposing risk factors may not eliminate the risk of perforation [9].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of major complications owing to esophageal perforation in transesophageal echocardiography (TEE) is generally low, with a complication rate of <3% and often <1% . Perforation occurs most often in the right piriform sinus, but the reasons behind perforations in TEE are not well understood . Though few in number, almost all of the complications in TEE are related to trauma from blind esophageal intubation.…”
Section: Introductionmentioning
confidence: 99%
“…While the resistance at other levels can be understood and solved in real time by direct visualization or palpation with the finger of the endoscopist, owing to the proximal location of these levels, the resistance felt at the UES level can neither be visualized nor felt by the “blind” endoscopist. It is at this level where most perforations occur at the piriform sinus . Although rare, esophageal perforation leads to mediastinitis, which carries a reported mortality rate of as high as 60% …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation